Enabling Media : Infrastructures, imaginaries and cultural techniques in Swedish and Estonian visual arts education - Forsler, Ingrid (2020)
This dissertation explores the media environments of visual arts education in Sweden and Estonia and how educators understand, negotiate and enable this infrastructure. Based on the notion that the ongoing digitalization of the educational system in these countries makes established practices appear, it further discusses how visual arts education as a school subject is shaped in relation to different technologies for image making and school administration. The comparative perspective makes visible how these practices have emerged in specific cultural settings, including the historical development of compulsory education and the organization of teacher training in each country. The two-way relation in which media technologies used in education to some extent condition pedagogical practice at the same time as being dependent on the work of educators, is conceptualized in the title as enabling media. Theoretically, the dissertation draws on infrastructuralism, suggested by Peters (2015), as a unifying concept for media studies interested in the logistical qualities of media. By using this perspective to study schools as media environments, the dissertation builds on an established interest within medium theory on the relation between compulsory education and media technologies.